Ephemeral Infrastructures of Drug Smuggling Mobilities. (December 2021) - Guerrero C., Javier; Martin, Craig
The study of drug smuggling has often taken an organizational perspective whereby the structures of how smuggling is constituted predominate. Building on a growing body of scholarship addressing the networked complexities of drug smuggling this article considers the importance of distinct infrastructural arrangements. Its primary focus is on the materiality of drug smuggling infrastructures, and how the social, spatial and temporal qualities of these configurations overlap with licit mobility infrastructures, including intersections of visibility/invisibility, stability, and permanence. The core conceptual premise, drawn from Science and Technology Studies, is that drug smuggling mobilities are formed of ephemeral infrastructures that exhibit temporary, short-lived stability and permanence through the subversion of licit infrastructural configurations. Drawing on material from El Dorado Airport, Colombia, the paper examines the everyday artefacts which constitute these ephemeral infrastructures.